2013
DOI: 10.2139/ssrn.2329693
|View full text |Cite
|
Sign up to set email alerts
|

A Coexceedance Approach on Financial Contagion

Abstract: ACKNOWLEDGEMENTSForemost, I would like to express my sincere gratitude to my supervisor, Lu Liu, for her guide and persistent support. Not only has she taken her time and patience to give me a number of valuable suggestions, but also showed me the most suitable approach to address the research questions. She has always kept track of my thesis to ensure that I was on the right progress.I am also indebted to Tuan-Minh Nguyen at Department of Mathematics, who has always offered me his enthusiastic assistance to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Eichengreen et al (2012), by means of a dynamic factor model, assessed the impact of the 2008 crisis on the global banking system, finding that the heightened counterparty risks coupled with the deterioration of banks' loan portfolio heavily impacted the movement of banks' credit default swap spreads. Vo (2014) demonstrated the particular significance of market comovements in the case of extreme negative returns during the global financial crisis and the Eurozone crisis. Choudhry and Jayasekera (2015) showed that during the global financial crisis, betas increased for most firms.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Eichengreen et al (2012), by means of a dynamic factor model, assessed the impact of the 2008 crisis on the global banking system, finding that the heightened counterparty risks coupled with the deterioration of banks' loan portfolio heavily impacted the movement of banks' credit default swap spreads. Vo (2014) demonstrated the particular significance of market comovements in the case of extreme negative returns during the global financial crisis and the Eurozone crisis. Choudhry and Jayasekera (2015) showed that during the global financial crisis, betas increased for most firms.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%